Availability and Utilization of Mobile Technology Tools in Chemistry Education Instructional Delivery: A Survey Research - Blessing Chinyere Cleopas; Kesiena Jesse Ohwofasa (Scientia Publica Media, 2026)
The study investigated the availability and utilization of mobile technology tools in chemistry education instructional delivery: A survey research. The population of the study was all the 400 level and 300 level students in chemistry education, Department of Science Education, Federal University Otuoke. A total population sampling technique was used to purposively select all the students in 400 level (53) and 300 level (38) in chemistry education as the sample (91) for the study. Three instruments, which included a checklist and two questionnaire were used for the collection of data for the study. These were 10 items check list on the availability of mobile technology tools in chemistry education instructional delivery, a 10 items questionnaire on the utilization of mobile technology tools in chemistry education instructional delivery, and a 10 items questionnaire on challenges militating against mobile technology tools in chemistry education instructional delivery. Three purposes and research questions guided the study. Cronbach’s alpha was used to get a reliability index of 0.9 for each of the instruments for the study. Mean and standard deviation were used as statistical tools for data analysis. Findings revealed that students have technology tools for learning, but these tools are not maximally utilized. Also, prevailing issues abound, militating against the utilization of technology tools for teaching and learning. Significantly, the study has provided evidence on the availability of technology tools at students’ disposal and challenges contributing to under-utilization of these tools in teaching and learning to improve the performance of chemistry students. Recommendations included that adequate support, training of lecturers and students would enhance integration of technology tools, which would further aid teaching and learning and improve academic achievement of students in Federal University Otuoke.